2020
DOI: 10.1007/s42773-020-00071-1
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing soil water holding capacity and provision of a potassium source via optimization of the pyrolysis of bamboo biochar

Abstract: Rapid expansion of cultivated bamboo negatively impacts on biodiversity and soil microbial community. As such, it is important to properly manage and use bamboo to prevent and control such issues. This study focuses on optimizing pyrolysis conditions to produce bamboo biochar for agricultural soil amendment, particularly soil potassium (K) and water holding capacity. Bamboo chips were pyrolyzed under nitrogen gas at 400, 600, and 800 °C for 1 and 2 h of retention. A total of six biochar products were created: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The pH of RSWC was determined to be 8.02; this value is in accordance with the results presented in other studies [ 10 , 47 ] and emphasizes that the biochar obtained from biomass pyrolysis is a good improver for the soil [ 17 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The pH of RSWC was determined to be 8.02; this value is in accordance with the results presented in other studies [ 10 , 47 ] and emphasizes that the biochar obtained from biomass pyrolysis is a good improver for the soil [ 17 ].…”
Section: Resultssupporting
confidence: 89%
“…This is due to its characteristics, such as a relatively large surface area, high pH, high organic C content and the presence of functional groups that can bind to contaminants [ 11 , 12 , 13 , 14 , 15 ]. It can also be a good adsorbent material, as well as a material with catalytic properties [ 16 , 17 ]. In addition to bio-oil and biochar, biomass waste pyrolysis produces a gas fraction (known as bio-syngas), which can be collected and utilized as an alternative to fossil fuels [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous studies indicating that biochar not only helps to mitigate soil acidification but also improves the soil nutrient status [ 43 , 44 ]. This rise in soil pH is primarily due to BB high pH ( Table S1 ) and a high concentration of base ions in its ash, such as Ca, Mg, K, and Na, which may efficiently decrease soil hydrogen ions and exchangeable aluminum ions [ 45 ], and therefore improves the soil nutrients status [ 46 ]. The better nutrient availability observed in this study could be related to direct input from biochar [ 11 , 47 ] because biochar itself does have the ability to improve soil fertility [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The graphite‐like structure could act as a π‐acceptor and interact with the phenyl ring of fentanyls via π–π interactions, while O‐groups can interact with fentanyl via H‐bonding. Previous studies have reported that high pyrolysis temperature could generally lead to higher C% content and lower O% and H% content in biochar because of dehydration and decarboxylation reaction [30,31]. These characteristics could result in great difference in their extraction ability; therefore, the pyrolysis temperature should be carefully chosen in order to achieve the greatest performance.…”
Section: Resultsmentioning
confidence: 99%